Evaluasi Kinerja dan Distribusi Beban Sistem PLN-PLTS pada Perencanaan Instalasi MEP Gedung Dinas Perumahan Rakyat, Kawasan Permukiman dan Cipta Karya Provinsi Jawa Timur - Muchamad Salman Al Farisi; Ibrohim Ibrohim; Joko Joko; Subuh Isnur Haryudo (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The use of solar power plants (PLTS) in buildings is one way to improve energy efficiency and support the sustainable use of renewable energy. In the planning of the Mechanical, Electrical, and Plumbing (MEP) installation of the Public Housing, Settlement, and Human Settlements Office Building in East Java Province, the PLTS system was designed as part of a hybrid PLN-PLTS system. However, the energy utilization generated by the PLTS still needs to be evaluated to optimize its use for building loads. This study aims to determine the performance of the PLTS system based on simulation results using PVSyst software and to determine the optimal load distribution between the PLN and PLTS supplies. The research method used is descriptive research with a quantitative approach. The data used are secondary data obtained from MEP planning documents, including the PLTS system design and building load data. System performance simulations were performed using PVSyst software with two solar panel installation orientations: 9° azimuth and -171° azimuth. Next, the generated electrical energy was converted into active power to determine the load that can be supplied by the PLTS system. The research results show that the solar PV system is capable of generating 35,883 kWh of electricity per year from two solar panel installation orientations. The simulation yielded a Performance Ratio (PR) of 0.756 for the first orientation and 0.755 for the second, indicating good and stable system performance. Based on the load distribution results, the energy generated by the solar PV system is capable of supplying the lighting needs of three buildings: the Main Building, the North Building, and the West Building, with a total power requirement of 14,030 watts. These results indicate that the designed PLN-PLTS hybrid system not only functions as a backup source but can also be used directly to support building operational needs and reduce dependence on PLN electricity supply.